2006
DOI: 10.1029/2005jd006631
|View full text |Cite
|
Sign up to set email alerts
|

Eddy covariance fluxes of peroxyacetyl nitrates (PANs) and NOy to a coniferous forest

Abstract: [1] We employed a fast response thermal dissociation-chemical ionization mass spectrometer (TD-CIMS) system to measure eddy covariance fluxes of peroxyacetyl nitrate (PAN), peroxypropionyl nitrate (PPN) and peroxymethacryloyl nitrate (MPAN). Average PAN deposition velocities, V d (PAN), showed a daytime maximum of $10.0 mm s À1 ; however, deposition did not cease during nighttime periods. V d (PAN) was highly variable at night and increased when canopy elements were wet from either precipitation or dew formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
164
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(195 citation statements)
references
References 68 publications
27
164
4
Order By: Relevance
“…It has been suggested that a majority of the dry N flux to most vegetated surfaces is due to HNO 3 vapor although it makes up only 2-10% of the total NO y composition (Williams et al, 1997). However, this study, other measurements made during CELTIC (Turnipseed et al, 2006), and other recent work (Sparks et al, 2003) suggest that peroxynitrates deposit more readily to vegetation than was once thought and can make a significant contribution to the total NO y flux. Given the potential variation in total dry N driven by the compositional differences of NO y outlined above, we have used four scenarios devised to encompass the possible range of NO y -deposition values.…”
Section: Scaling To Annual Estimatescontrasting
confidence: 49%
See 2 more Smart Citations
“…It has been suggested that a majority of the dry N flux to most vegetated surfaces is due to HNO 3 vapor although it makes up only 2-10% of the total NO y composition (Williams et al, 1997). However, this study, other measurements made during CELTIC (Turnipseed et al, 2006), and other recent work (Sparks et al, 2003) suggest that peroxynitrates deposit more readily to vegetation than was once thought and can make a significant contribution to the total NO y flux. Given the potential variation in total dry N driven by the compositional differences of NO y outlined above, we have used four scenarios devised to encompass the possible range of NO y -deposition values.…”
Section: Scaling To Annual Estimatescontrasting
confidence: 49%
“…These tests (conducted upon each calibration) also indicated an adequately fast response (to0.5 s, 1/e). The conversion efficiencies and losses of NO y within our system are discussed more fully in Turnipseed et al (2006). Simply stated, it is likely that there was some loss of HNO 3 within the initial inlet, although the exact amount of loss under the experimental conditions was difficult to quantify.…”
Section: Long-term Data Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent field study over a coniferous forest (Turnipseed et al, 2006;Sparks et al, 2008) estimated that HNO 3 accounted for only w24% of the NO y flux and PAN exhibited a close portion of w20%. Zhang et al (2009) investigated the total nitrogen flux budget over eight rural sites across eastern Canada, and estimated that HNO 3 constituted less than half of the NO y flux (46%), and the flux from other measured gaseous nitrogen species (NO 2 þ PAN þ PPN) were also a significant portion (35%).…”
Section: Evaluation Of Modeled V D (No Y )mentioning
confidence: 99%
“…Measuring deposition fluxes for reactive nitrogen compounds and O 3 with the eddy-covariance technique (e.g. Munger et al, 1996;Turnipseed et al, 2006) or the gradient method (e.g. Meyers et al, 1989;Sievering et al, 2001) have formed the basis for deposition models aimed at predicting dry depositions of reactive nitrogen compounds and O 3 .…”
Section: Introductionmentioning
confidence: 99%